Analysis of Taxpayer Compliance in Paying Land and Building Tax in Simpang Tanjung Village - Wahyu Miko Pratama; Salsabila Nadhifa Althaaf; Frennando Dewa Chandika; Vina Arnita (Proceeding of The International Conference on Business and Economics, 2024)
This study aims to determine the level of taxpayer compliance in paying Land and Building Tax in Simpang Tanjung Village. What obstacles are experienced by taxpayers and how to solve problems regarding Land and Building Tax in Simpang Tanjung Village, this study design uses descriptive analysis where data is collected through observation. The result of the study show that the housing sector dominates the majority of taxpayers by 65%, followed by commercial 25% and public facilities 10% and the level of taxpayers compliance in Simpang Tanjung Village increases by 1% each year, this indicates that taxpayer participation in paying their taxes tends to be positive.